The first signs of glaucomatous cupping in the optic nerve - Anderson, Douglas (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Evaluation of the optic disc is important for both the diagnosis of glaucoma, and in monitoring the progress of glaucoma. Along with visual field examination, it allows the presence of glaucoma to be recognized, and for progressive damage to be seen. Glaucoma can occur despite intraocular pressure (IOP) in the normal range, but as importantly, can be absent even when the IOP is distinctly high.